The petrology and geochemistry of the Vogelstruisbult Annex Cu-Zn deposit, Prieska district, north-western Cape - Scheepers, D. J.(Deon Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1989.